(untitled) (Journal of Pharmaceutical Negative Results, 2023)
It is the need of time to use the revolution in the field of technology to update the science. Modern medical scientists have used this technology to enrich medical science and this is one of the reasons for its global acceptance. Reaction Time Analyzer is a scientific, accurate, and sophisticated instrument that measures the speed of a reaction. With the help of a reaction time analyzer, it is possible to demonstrate the speed of reaction, which is one of the activity of Vata Dosha and it is possible that it differs according to Sharir Prakruti. According to Ayurveda each individual is of a specific constitution as per the predominance of Dosha. Hence, this topic was selected as an attempt to make use of a Reaction Time Analyzer, for the study of whether there is any association of reaction time with Sharir Prakruti And to project it as a model for the study of basic concepts in Ayurveda. This is a fundamental type of study and it is limited to visual, stimuli. A total of 680 subjects were screened. From these, only 620 subjects were included in the study. There is scope for study on the large sample in various physiological conditions and in different groups. This work aimed to project the use of a Reaction Time Analyzer as a model for the study of basic concepts of Ayurveda and to study the relationship between the Prakruti & Reaction time. Project work was planned and executed accordingly. All the references from Ayurvedic Literature regarding, Tridosha, and Prakṛuti Indriyas, modern textbooks on sensory & motor system, reflex action, and reaction were studied. Detail information & working of R.T.A. equipment was studied. Prakruti of each subject included in the study was determined by using the standard Proforma of AYUSOFT -C-DAC. Reaction time was recorded by using R.T.A. in different conditions; as per group. The data collected were statistically analyzed. Data was interpreted & conclusions were drawn.